(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The interactions of protein Ligand play important in built of many drugs design, so by Appling: molecular docking, to identify and investigated their affinity of hyroxy-tyrosol in androgen receptor. The structural a three dimensional (3D) of androgen receptor was Protein Data Bank chosen, then 3D docken with of tested compound. The results represent that (hydroxyl-tyrosol) exhibited best binding affinity of −6.2 kcal/ mol with AR followed by anastrazole−5.2 kcal/ mol. A total Thirty Mature Wister male albino rats . Adult Thirty male rats were equally and randomly distributed into 3rd groups of ten animals for each group. The first group, named as negative control (NC), The second group(T1) and (T2) daily orally received HT extract (50 mg/kg as free and nanoparticles respectively. The antioxidant capacity of HT by scavenging of ROS and clear improvement of reproductive function and testicular tissues.